1995
DOI: 10.1093/oxfordjournals.jbchem.a124882
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Ras-Transformed Cells Becomes Apparently Normal Again with Tyrosine Kinase Inhibitors without a Decrease in the Ras-GTP Complex1

Abstract: Radicicol, an inhibitor of protein-tyrosine kinase, was found to cause morphological reversion of v-Ha-ras-transformed NIH3T3 fibroblasts and T24 human urinary bladder carcinoma cells that contain an activated ras mutation. The network of actin stress fibers was restored during the treatment with radicicol. A similar morphological change was observed with another protein-tyrosine kinase inhibitor, herbimycin A. Radicicol did not cause any changes in the proportion of the active GTP binding form of p21ras or it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…With this goal in mind, a biotinylated derivative of radicicol was synthesized. The structure of radicicol (shown in Figure 1b) contains an epoxide residue that is critical for its antifungal properties (Ayer et al, 1980) and may play a role in its biological activity as a tyrosine kinase inhibitor (Kwon et al, 1992a). In addition, radicicol, like many other tyrosine kinase inhibitors, possesses phenolic ring structures that may be necessary for its function.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With this goal in mind, a biotinylated derivative of radicicol was synthesized. The structure of radicicol (shown in Figure 1b) contains an epoxide residue that is critical for its antifungal properties (Ayer et al, 1980) and may play a role in its biological activity as a tyrosine kinase inhibitor (Kwon et al, 1992a). In addition, radicicol, like many other tyrosine kinase inhibitors, possesses phenolic ring structures that may be necessary for its function.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are especially germane in light of recent ®ndings that radicicol treatment of K-Ras transformed cells leads to the selective degradation of Raf-1 and a concomitant suppression of the transformed phenotype (Soga et al, 1998). In addition, previous studies have shown that radicicol treatment attenuates the MAP kinase pathway in vivo (Zhao et al, 1995), but has little or no e ect on the in vitro activity of MAP kinase (Kwon et al, 1995). In its inactive state Raf exists as a cytosolic multi-protein complex, associated with proteins such as HSP90, Cdc37/p50 and 14-3-3.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations